A protocol for eliciting nonmaterial values through a cultural ecosystem services frame. Issue 2 (29th October 2014) - Gould, Rachelle K.; Klain, Sarah C.; Ardoin, Nicole M.; Satterfield, Terre; Woodside, Ulalia; Hannahs, Neil; Daily, Gretchen C.; Chan, Kai M.
Abstract Stakeholders' nonmaterial desires, needs, and values often critically influence the success of conservation projects. These considerations are challenging to articulate and characterize, resulting in their limited uptake in management and policy. We devised an interview protocol designed to enhance understanding of cultural ecosystem services (CES). The protocol begins with discussion of ecosystem‐related activities (e.g., recreation, hunting) and management and then addresses CES, prompting for values encompassing concepts identified in the Millennium Ecosystem Assessment (2005) and explored in other CES research. We piloted the protocol in Hawaii and British Columbia. In each location, we interviewed 30 individuals from diverse backgrounds. We analyzed results from the 2 locations to determine the effectiveness of the interview protocol in elucidating nonmaterial values. The qualitative and spatial components of the protocol helped characterize cultural, social, and ethical values associated with ecosystems in multiple ways. Maps and situational, or vignette‐like, questions helped respondents articulate difficult‐to‐discuss values. Open‐ended prompts allowed respondents to express a diversity of ecosystem‐related values and proved sufficiently flexible for interviewees to communicate values for which the protocol did not explicitly probe. Finally, the results suggest that certain values, those mentioned frequently throughout the interview, are particularly salient for particular populations. The protocol can provide efficient, contextual, and place‐based data on the importance of particular ecosystem attributes for human well‐being. Qualitative data are complementary to quantitative and spatial assessments in the comprehensive representation of people's values pertaining to ecosystems, and this protocol may assist in incorporating values frequently overlooked in decision making processes.